1990
DOI: 10.1111/j.1469-8749.1990.tb08427.x
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Co‐Ordination Of Sucking, Swallowing And Breathing: Ultrasound Study Of Term And Preterm Infants

Abstract: SUMMARY Fourteen newborn babies of different gestational ages (33 to 40 weeks) but similar postnatal age (four to 19 days) were studied during bottle‐feeding using real‐time ultrasonography, combined with respiratory monitoring. Previously undescribed tongue movements and graded changes in the temporal relationships between tongue movements, swallowing and breathing were observed among infants of differing maturity. These were most marked in the least mature infants, but were occasionally seen in term infants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
2
15

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(141 citation statements)
references
References 18 publications
3
121
2
15
Order By: Relevance
“…These findings are consistent with the findings of previous studies of preterm neonates, which have reported that suckling skills [6][7][8] and the coordination of suckling, swallowing and breathing [9][10][11][12][13][14][15] improve with ongoing maturity. These findings are also consistent with previous studies that have suggested that certain morbidities affecting body-systems involved in feeding, such as the respiratory and circulatory systems, may affect the efficiency of suckle-feeding in preterm neonates.…”
Section: Attainment Of Exclusive Suckle-feedssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the findings of previous studies of preterm neonates, which have reported that suckling skills [6][7][8] and the coordination of suckling, swallowing and breathing [9][10][11][12][13][14][15] improve with ongoing maturity. These findings are also consistent with previous studies that have suggested that certain morbidities affecting body-systems involved in feeding, such as the respiratory and circulatory systems, may affect the efficiency of suckle-feeding in preterm neonates.…”
Section: Attainment Of Exclusive Suckle-feedssupporting
confidence: 92%
“…5 Depending on their GA at birth, preterm neonates may display various degrees of immaturity of their nervous, anatomical and physiological control systems, which have the potential to affect the strength, coordination and efficiency of the skills required for suckle-feeding. Several studies have documented that for preterm neonates, suckling skills [6][7][8] and the coordination of suckling, swallowing and breathing [9][10][11][12][13][14][15] improve with ongoing post-natal maturation. However, few studies have specifically investigated the relationship between GA at birth and either GA at commencement of suckle-feeds or GA at attainment of exclusive suckle-feeding.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of swallow-respiration and suck-swallow rhythms may be predictive of feeding, respiratory and neurodevelopmental abnormalities. 23 Infants with BPD, however, do not follow predicted maturational patterns of sucking-swallowing rhythmic integration. A follow-up study of Gewolb and Vice 32 suggests that ventilatory needs may modulate sucking rhythm and organization.…”
Section: Introductionmentioning
confidence: 89%
“…Feeding activity appears to override normal ventilatory chemoreceptor control mechanisms 23 and the act of swallowing has a significant impact on breathing during feeding. As infants commonly swallow as often as 60 times a minute, and there is an airway closure averaging 530 ms associated with swallows, this means that during the initial period of continuous sucking, the airway closure lasts up to 30 s a minute.…”
Section: Introductionmentioning
confidence: 99%
“…The infant may demonstrate rudimentary components of sucking and swallowing by 28 weeks gestation. 155 At about 32 weeks gestation, an infant will begin to display bursts of sucking, and by 34 weeks a rhythmic suck, swallow and breathe pattern is developing. [156][157][158][159][160][161] Non-nutritive sucking will transition towards more effective nutritive sucking, concurrent with state of alertness and increasing gestational age.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%